Fluoride Contents Analysis of Tea Infusion, Mouthwash and Tooth Paste Samples of Pakistan Using Ion Selective Electrode - Rehman, Rabia; Khalid, Maria (Asian Journal of Chemistry, 2015)
Potentiometric analysis of fluoride is carried out in tea, tooth paste and mouth wash/teeth whitener samples which are commonly used in Pakistan using fluoride ion selective electrode. Due to lack of awareness and contaminated plus adulterated food usage, dental and skeletal fluorosis increased in different areas. The analysis of locally available samples of tea, tooth paste and mouthwash indicated that the concentration of fluoride is within the threshold limits in branded samples, but their excessive use should be minimized for avoiding fluorosis.